Causes of Mortality in Acute and Chronic Renal Failure - Taş, Ferdi Seyyid; Cengiz, Kuddusi; Erdem, Emre; Karataş, Ahmet; Kaya, Coşkun (Fırat University, 2011)
Objective: Acute and chronic renal failure have high mortality rate and increased incidence with aging. In this study; we aim to investigate the mortality causes in the population of patients who were referred to our hospital because of acute or chronic renal failure and then died. Materials and Methods: This study was performed between June 2007 and June 2010 by examining files of 240 renal failure patient's retrospectively who were admitted to emergency room and our internal medicine clinic and then died. We investigated the mortality causes, etiologies of renal failure, accompanying systemic diseases and whether dialysis performed after admission to the hospital or not in the population of patients who were referred to our hospital because of acute or chronic renal failure and then died. Results: Among 240 patients; 96 patients had acute renal failure (ARF) and 144 had chronic renal failure (CRF). The median age of ARF patients was 71.3±11.9 while CRF patients' median age was 65.5±13.9. Sepsis and hypovolemia were the main causes of ARF. The common causes of CRF were diabetes mellitus and hypertension. While 45.8% of ARF patients undergone hemodialysis, this ratio was 60% for predialysis CRF patients .Infection was the cause of mortality in 64.6% of ARF patients and 68,8% of CRF patients. In both groups the second leading cause of mortality was cardiovascular diseases. Conclusion: In our study, infection was the most common cause of mortality in ARF and CRF patients admitted to hospital.

Amaç: Akut ve kronik böbrek yetmezliği, ileri yaşla birlikte görülme insidansları giderek artan, mortalite oranları yüksek hastalıklardır. Çalışmamızın amacı, akut veya kronik böbrek yetmezliği nedeni ile hastanemize başvurup ölen hastalarda mortalite nedenlerini araştırmaktır. Gereç ve Yöntem: Araştırma, Haziran 2007 ile Haziran 2010 tarihleri arasında acil servis ve dahiliye kliniğimize başvurup ölen böbrek yetmezliği tanılı 240 hastanın kayıtları retrospektif incelenerek yapılmıştır. Akut veya kronik böbrek yetmezliği nedeni ile hastanemize başvurup ölen hastaların mortalite nedenlerine, böbrek yetmezliği etiyolojilerine, eşlik eden diğer sistemik hastalıklarına, hastaneye başvurduktan sonra diyalize alınıp alınmadıklarına bakılmıştır. Bulgular: 240 hastanın 96'sında akut böbrek yetmezliği (ABY), 144'ünde kronik böbrek yetmezliği (KBY) vardı. ABY tanılı ölen hastaların yaş ortalaması 71.3±11.9 iken KBY tanılı ölen hastaların yaş ortalaması 65.5±13.9 idi. Sepsis ve hipovolemi ABY'ne yol açan en sık nedenlerdi. KBY hastalarında en sık etiyolojik nedenler diyabet ve hipertansiyondu. ABY nedeni ile başvuran hastaların %45.8‘i hemodiyalize alınırken, prediyaliz KBY olan hastaların %60'ı hemodiyalize alınmıştı. ABY olan hastaların %64.6'sında KBY olan hastaların %68.8'inde ölüm nedeni enfeksiyon hastalıkları idi. Her iki grupta en sık ikinci ölüm nedeni kardiovasküler hastalıklardı. Sonuç: Akut ve kronik böbrek yetmezliği tanısı ile başvuran hastalarda en sık mortalite nedeni enfeksiyon hastalıkları bulunmuştur.
Akut ve Kronik Böbrek Yetmezliğinde Mortalite Nedenleri